2020
DOI: 10.1109/access.2020.2985290
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Deep Learning Algorithms Factors in Software Fault Prediction

Abstract: The discovery of software faults at early stages plays an important role in improving software quality; reduce the costs, time, and effort that should be spent on software development. Machine learning (ML) have been widely used in the software faults prediction (SFP), ML algorithms provide varying results in terms of predicting software fault. Deep learning achieves remarkable performance in various areas such as computer vision, natural language processing, speech recognition, and other fields. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…The study 14 It has been found that the proposed system outperformed existing system by showing high accuracy percentage of 99.01%. Thus the proposed MLP has shown high accuracy in classifying the SFP which reveal its efficiency than the traditional methods.…”
Section: Comparative Analysis With Respect To Accuracymentioning
confidence: 89%
See 2 more Smart Citations
“…The study 14 It has been found that the proposed system outperformed existing system by showing high accuracy percentage of 99.01%. Thus the proposed MLP has shown high accuracy in classifying the SFP which reveal its efficiency than the traditional methods.…”
Section: Comparative Analysis With Respect To Accuracymentioning
confidence: 89%
“…TA B L E 1 Comparative analysis of the proposed and existing methods 14 The proposed system is compared with the existing methods with respect to error rate and it is shown in Table 2. The existing methods such as RF, LR, CART, and MLP are considered.…”
Section: Comparative Analysis With Respect To Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…19 . These factors include the number of samples [ 89 ], the number of layers [ 89 , 103 ], the number of classes [ 25 ], the image modality and quality [ 104 ], and the hyperparameters values [ 85 , 103 ]. For instance, AlexNet achieved the highest sensitivity and specificity of 100% in the binary classification of a brain tumor in MRI images [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fault prediction techniques are developed to minimize time and cost in maintenance and testing phases in the software development lifecycle and to develop a safe and efficient system. Machine learning and deep learning are commonly used in predicting software faults and utilized in diverse research fields 8‐14 . One of the techniques that are used for optimization and prediction is called Genetics algorithm, and it is defined by Reference 15 as “a problem‐solving algorithm that uses genetics as a model of problem‐solving, also It's a search technique to find approximate solutions to optimization and search problems”.…”
Section: Introductionmentioning
confidence: 99%